Distinction of mixed yam strains (Dioscorea alata L.) cultivated in Yaku Island - Onjo, M.; Matsuo, T.; Hakariya, S.; Shiwachi, H.; Hayashi, M. (2003)
This study clarified we could effectively distinguish mixed water yam strains by observing the differences of morphology of the leaves and tubers in Yaku Island. However, there are considerable variations in morphology, so we may be able to more confidently distinguish strains by also employing the electrophoresis method using acetone powder.